2018
DOI: 10.1002/bies.201700235
|View full text |Cite
|
Sign up to set email alerts
|

DNA Conformation Regulates Gene Expression: The MYC Promoter and Beyond

Abstract: Emerging evidence suggests that DNA topology plays an instructive role in cell fate control through regulation of gene expression. Transcription produces torsional stress, and the resultant supercoiling of the DNA molecule generates an array of secondary structures. In turn, local DNA architecture is harnessed by the cell, acting within sensory feedback mechanisms to mediate transcriptional output. MYC is a potent oncogene, which is upregulated in the majority of cancers; thus numerous studies have focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 133 publications
(194 reference statements)
1
8
0
Order By: Relevance
“…Indeed, it has been shown that FUBP1 can contribute to a feedforward/feedback system that regulates Myc transcription in real-time. FUBP1 has been proposed to be a key effector that can both up- or downregulate MYC and behave as a molecular cruise control that opposes MYC fluctuations 29 , 32 , 45 , 69 . The superposition of multiple layers on Myc regulation might argue that its expression has been selected to be more tightly controlled than most other genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, it has been shown that FUBP1 can contribute to a feedforward/feedback system that regulates Myc transcription in real-time. FUBP1 has been proposed to be a key effector that can both up- or downregulate MYC and behave as a molecular cruise control that opposes MYC fluctuations 29 , 32 , 45 , 69 . The superposition of multiple layers on Myc regulation might argue that its expression has been selected to be more tightly controlled than most other genes.…”
Section: Discussionmentioning
confidence: 99%
“…Of the multiple regions that regulate MYC expression, we have been interested in the far upstream element (FUSE), which is 1.7 kb upstream of the major P2 transcription start site of human MYC gene and binds FUBP1 23 , 29 – 36 . The FUSE-binding protein (FUBP) family has three members in human and mouse—FUBP1, FUBP2/KHSRP, and FUBP3 23 , 29 – 35 , 37 , 38 —and only one in Drosophil a—Psi 31 , 32 , 37 , 39 . FUBP1 is both prooncogenic and a tumor suppressor 37 , 40 , 41 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…c-Myc is a conventional transcriptional factor. By binding to the cis- regulatory element E-box (CACGTG) of its transactivated genes, c-Myc plays an essential role in the regulation of many biological processes including cell cycle, cell proliferation, apoptosis and cell metabolism23-25. c-Myc has been reported to be upregulated in a variety of carcinomas including RCC.…”
Section: Discussionmentioning
confidence: 99%